Theta and alpha oscillatory responses differentiate between six-to seven-year-old children and adults during successful visual and auditory memory encoding - Güntekin, Bahar; Uzunlar, Hakan; Çalışoğlu, Pervin; Eroğlu-Ada, Figen; Yıldırım, Ebru; Aktürk, Tuba; Atay, Enver; Ceran, Ömer (Elsevier, 2020)
The healthy maturation of the brain is one of the intriguing topics that need to be investigated to understand human brain and child development. The present study aimed to investigate the development of memory processes both for auditory and visual memory using electroencephalography (EEG)-Brain Dynamics methodologies.Sixteen healthy children between the ages of 6 and 7 years and eighteen healthy young adults (age: 21.32 +/- 3.28 years) were included in the study. EEG was recorded from 18 channels during the visual and auditory memory paradigms. Two different subtests of the WISC-IV IQ test were applied to all children. Eventrelated theta (4-7 Hz), alpha (8-13 Hz) power and phase-locking were analyzed.The young adults had higher memory performance than the children for both auditory and visual paradigms. The children had increased theta phase-locking and left alpha power in response to the remembered objects in comparison to the forgotten objects. The young adults had higher theta and alpha phase-locking than the children over the frontal and central locations (p < 0.05), and the children had higher parietal-occipital alpha phase-locking than the young adults. There was an increase in alpha power in children, whereas young adults had decreased post-stimulus alpha power in response to memory paradigms.The present study showed that frontocentral theta and alpha phase-locking had an essential role in brain maturation and successful memory performance. Event-related theta and alpha responses could be one of the important indicators of the mature and healthy brain, and these responses could change depending on the maturation state and age.
Keywords: EEG; Child; Memory; Event-Related Oscillations; Phase-Locking; Theta